Examples
B=[987345210]B=⎡⎢⎣987345210⎤⎥⎦
Step 1
Set up the formula to find the characteristic equation p(λ)p(λ).
p(λ)=determinant(A-λI3)p(λ)=determinant(A−λI3)
Step 2
The identity matrix or unit matrix of size 33 is the 3×33×3 square matrix with ones on the main diagonal and zeros elsewhere.
[100010001]⎡⎢⎣100010001⎤⎥⎦
Step 3
Step 3.1
Substitute [987345210]⎡⎢⎣987345210⎤⎥⎦ for AA.
p(λ)=determinant([987345210]-λI3)p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦−λI3⎞⎟⎠
Step 3.2
Substitute [100010001]⎡⎢⎣100010001⎤⎥⎦ for I3I3.
p(λ)=determinant([987345210]-λ[100010001])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦−λ⎡⎢⎣100010001⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]-λ[100010001])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦−λ⎡⎢⎣100010001⎤⎥⎦⎞⎟⎠
Step 4
Step 4.1
Simplify each term.
Step 4.1.1
Multiply -λ−λ by each element of the matrix.
p(λ)=determinant([987345210]+[-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2
Simplify each element in the matrix.
Step 4.1.2.1
Multiply -1−1 by 11.
p(λ)=determinant([987345210]+[-λ-λ⋅0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ−λ⋅0−λ⋅0−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.2
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.2.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ0λ-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ0λ−λ⋅0−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.2.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ0−λ⋅0−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ0-λ⋅0-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ0−λ⋅0−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.3
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.3.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ00λ-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ00λ−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.3.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ00-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ00−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ00-λ⋅0-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ00−λ⋅0−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.4
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.4.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ000λ-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000λ−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.4.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ000-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ⋅1-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ⋅1−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.5
Multiply -1−1 by 11.
p(λ)=determinant([987345210]+[-λ000-λ-λ⋅0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ−λ⋅0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.6
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.6.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ000-λ0λ-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ0λ−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.6.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ000-λ0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ0-λ⋅0-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ0−λ⋅0−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.7
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.7.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ000-λ00λ-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ00λ−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.7.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ000-λ00-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ00−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ00-λ⋅0-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ00−λ⋅0−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.8
Multiply -λ⋅0−λ⋅0.
Step 4.1.2.8.1
Multiply 00 by -1−1.
p(λ)=determinant([987345210]+[-λ000-λ000λ-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000λ−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.8.2
Multiply 00 by λλ.
p(λ)=determinant([987345210]+[-λ000-λ000-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000−λ⋅1⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ000-λ⋅1])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000−λ⋅1⎤⎥⎦⎞⎟⎠
Step 4.1.2.9
Multiply -1−1 by 11.
p(λ)=determinant([987345210]+[-λ000-λ000-λ])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000−λ⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ000-λ])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000−λ⎤⎥⎦⎞⎟⎠
p(λ)=determinant([987345210]+[-λ000-λ000-λ])p(λ)=determinant⎛⎜⎝⎡⎢⎣987345210⎤⎥⎦+⎡⎢⎣−λ000−λ000−λ⎤⎥⎦⎞⎟⎠
Step 4.2
Add the corresponding elements.
p(λ)=determinant[9-λ8+07+03+04-λ5+02+01+00-λ]p(λ)=determinant⎡⎢⎣9−λ8+07+03+04−λ5+02+01+00−λ⎤⎥⎦
Step 4.3
Simplify each element.
Step 4.3.1
Add 88 and 00.
p(λ)=determinant[9-λ87+03+04-λ5+02+01+00-λ]p(λ)=determinant⎡⎢⎣9−λ87+03+04−λ5+02+01+00−λ⎤⎥⎦
Step 4.3.2
Add 77 and 00.
p(λ)=determinant[9-λ873+04-λ5+02+01+00-λ]p(λ)=determinant⎡⎢⎣9−λ873+04−λ5+02+01+00−λ⎤⎥⎦
Step 4.3.3
Add 33 and 00.
p(λ)=determinant[9-λ8734-λ5+02+01+00-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ5+02+01+00−λ⎤⎥⎦
Step 4.3.4
Add 55 and 00.
p(λ)=determinant[9-λ8734-λ52+01+00-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ52+01+00−λ⎤⎥⎦
Step 4.3.5
Add 22 and 00.
p(λ)=determinant[9-λ8734-λ521+00-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ521+00−λ⎤⎥⎦
Step 4.3.6
Add 11 and 00.
p(λ)=determinant[9-λ8734-λ5210-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ5210−λ⎤⎥⎦
Step 4.3.7
Subtract λλ from 00.
p(λ)=determinant[9-λ8734-λ521-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ521−λ⎤⎥⎦
p(λ)=determinant[9-λ8734-λ521-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ521−λ⎤⎥⎦
p(λ)=determinant[9-λ8734-λ521-λ]p(λ)=determinant⎡⎢⎣9−λ8734−λ521−λ⎤⎥⎦
Step 5
Step 5.1
Choose the row or column with the most 00 elements. If there are no 00 elements choose any row or column. Multiply every element in row 11 by its cofactor and add.
Step 5.1.1
Consider the corresponding sign chart.
|+-+-+-+-+|∣∣
∣∣+−+−+−+−+∣∣
∣∣
Step 5.1.2
The cofactor is the minor with the sign changed if the indices match a -− position on the sign chart.
Step 5.1.3
The minor for a11a11 is the determinant with row 11 and column 11 deleted.
|4-λ51-λ|∣∣∣4−λ51−λ∣∣∣
Step 5.1.4
Multiply element a11a11 by its cofactor.
(9-λ)|4-λ51-λ|(9−λ)∣∣∣4−λ51−λ∣∣∣
Step 5.1.5
The minor for a12a12 is the determinant with row 11 and column 22 deleted.
|352-λ|∣∣∣352−λ∣∣∣
Step 5.1.6
Multiply element a12a12 by its cofactor.
-8|352-λ|−8∣∣∣352−λ∣∣∣
Step 5.1.7
The minor for a13a13 is the determinant with row 11 and column 33 deleted.
|34-λ21|∣∣∣34−λ21∣∣∣
Step 5.1.8
Multiply element a13a13 by its cofactor.
7|34-λ21|7∣∣∣34−λ21∣∣∣
Step 5.1.9
Add the terms together.
p(λ)=(9-λ)|4-λ51-λ|-8|352-λ|+7|34-λ21|p(λ)=(9−λ)∣∣∣4−λ51−λ∣∣∣−8∣∣∣352−λ∣∣∣+7∣∣∣34−λ21∣∣∣
p(λ)=(9-λ)|4-λ51-λ|-8|352-λ|+7|34-λ21|p(λ)=(9−λ)∣∣∣4−λ51−λ∣∣∣−8∣∣∣352−λ∣∣∣+7∣∣∣34−λ21∣∣∣
Step 5.2
Evaluate |4-λ51-λ|∣∣∣4−λ51−λ∣∣∣.
Step 5.2.1
The determinant of a 2×22×2 matrix can be found using the formula |abcd|=ad-cb∣∣∣abcd∣∣∣=ad−cb.
p(λ)=(9-λ)((4-λ)(-λ)-1⋅5)-8|352-λ|+7|34-λ21|p(λ)=(9−λ)((4−λ)(−λ)−1⋅5)−8∣∣∣352−λ∣∣∣+7∣∣∣34−λ21∣∣∣
Step 5.2.2
Simplify the determinant.
Step 5.2.2.1
Simplify each term.
Step 5.2.2.1.1
Apply the distributive property.
p(λ)=(9-λ)(4(-λ)-λ(-λ)-1⋅5)-8|352-λ|+7|34-λ21|p(λ)=(9−λ)(4(−λ)−λ(−λ)−1⋅5)−8∣∣∣352−λ∣∣∣+7∣∣∣34−λ21∣∣∣
Step 5.2.2.1.2
Multiply -1 by 4.
p(λ)=(9-λ)(-4λ-λ(-λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.3
Rewrite using the commutative property of multiplication.
p(λ)=(9-λ)(-4λ-1⋅-1λ⋅λ-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4
Simplify each term.
Step 5.2.2.1.4.1
Multiply λ by λ by adding the exponents.
Step 5.2.2.1.4.1.1
Move λ.
p(λ)=(9-λ)(-4λ-1⋅-1(λ⋅λ)-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.1.2
Multiply λ by λ.
p(λ)=(9-λ)(-4λ-1⋅-1λ2-1⋅5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ-1⋅-1λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.2
Multiply -1 by -1.
p(λ)=(9-λ)(-4λ+1λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.4.3
Multiply λ2 by 1.
p(λ)=(9-λ)(-4λ+λ2-1⋅5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ+λ2-1⋅5)-8|352-λ|+7|34-λ21|
Step 5.2.2.1.5
Multiply -1 by 5.
p(λ)=(9-λ)(-4λ+λ2-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(-4λ+λ2-5)-8|352-λ|+7|34-λ21|
Step 5.2.2.2
Reorder -4λ and λ2.
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8|352-λ|+7|34-λ21|
Step 5.3
Evaluate |352-λ|.
Step 5.3.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(9-λ)(λ2-4λ-5)-8(3(-λ)-2⋅5)+7|34-λ21|
Step 5.3.2
Simplify each term.
Step 5.3.2.1
Multiply -1 by 3.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-2⋅5)+7|34-λ21|
Step 5.3.2.2
Multiply -2 by 5.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7|34-λ21|
Step 5.4
Evaluate |34-λ21|.
Step 5.4.1
The determinant of a 2×2 matrix can be found using the formula |abcd|=ad-cb.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3⋅1-2(4-λ))
Step 5.4.2
Simplify the determinant.
Step 5.4.2.1
Simplify each term.
Step 5.4.2.1.1
Multiply 3 by 1.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-2(4-λ))
Step 5.4.2.1.2
Apply the distributive property.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-2⋅4-2(-λ))
Step 5.4.2.1.3
Multiply -2 by 4.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8-2(-λ))
Step 5.4.2.1.4
Multiply -1 by -2.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8+2λ)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(3-8+2λ)
Step 5.4.2.2
Subtract 8 from 3.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(-5+2λ)
Step 5.4.2.3
Reorder -5 and 2λ.
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
p(λ)=(9-λ)(λ2-4λ-5)-8(-3λ-10)+7(2λ-5)
Step 5.5
Simplify the determinant.
Step 5.5.1
Simplify each term.
Step 5.5.1.1
Expand (9-λ)(λ2-4λ-5) by multiplying each term in the first expression by each term in the second expression.
p(λ)=9λ2+9(-4λ)+9⋅-5-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2
Simplify each term.
Step 5.5.1.2.1
Multiply -4 by 9.
p(λ)=9λ2-36λ+9⋅-5-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.2
Multiply 9 by -5.
p(λ)=9λ2-36λ-45-λ⋅λ2-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3
Multiply λ by λ2 by adding the exponents.
Step 5.5.1.2.3.1
Move λ2.
p(λ)=9λ2-36λ-45-(λ2λ)-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.2
Multiply λ2 by λ.
Step 5.5.1.2.3.2.1
Raise λ to the power of 1.
p(λ)=9λ2-36λ-45-(λ2λ1)-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.2.2
Use the power rule aman=am+n to combine exponents.
p(λ)=9λ2-36λ-45-λ2+1-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ2+1-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.3.3
Add 2 and 1.
p(λ)=9λ2-36λ-45-λ3-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3-λ(-4λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.4
Rewrite using the commutative property of multiplication.
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ⋅λ-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.5
Multiply λ by λ by adding the exponents.
Step 5.5.1.2.5.1
Move λ.
p(λ)=9λ2-36λ-45-λ3-1⋅-4(λ⋅λ)-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.5.2
Multiply λ by λ.
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3-1⋅-4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.6
Multiply -1 by -4.
p(λ)=9λ2-36λ-45-λ3+4λ2-λ⋅-5-8(-3λ-10)+7(2λ-5)
Step 5.5.1.2.7
Multiply -5 by -1.
p(λ)=9λ2-36λ-45-λ3+4λ2+5λ-8(-3λ-10)+7(2λ-5)
p(λ)=9λ2-36λ-45-λ3+4λ2+5λ-8(-3λ-10)+7(2λ-5)
Step 5.5.1.3
Add 9λ2 and 4λ2.
p(λ)=13λ2-36λ-45-λ3+5λ-8(-3λ-10)+7(2λ-5)
Step 5.5.1.4
Add -36λ and 5λ.
p(λ)=13λ2-31λ-45-λ3-8(-3λ-10)+7(2λ-5)
Step 5.5.1.5
Apply the distributive property.
p(λ)=13λ2-31λ-45-λ3-8(-3λ)-8⋅-10+7(2λ-5)
Step 5.5.1.6
Multiply -3 by -8.
p(λ)=13λ2-31λ-45-λ3+24λ-8⋅-10+7(2λ-5)
Step 5.5.1.7
Multiply -8 by -10.
p(λ)=13λ2-31λ-45-λ3+24λ+80+7(2λ-5)
Step 5.5.1.8
Apply the distributive property.
p(λ)=13λ2-31λ-45-λ3+24λ+80+7(2λ)+7⋅-5
Step 5.5.1.9
Multiply 2 by 7.
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ+7⋅-5
Step 5.5.1.10
Multiply 7 by -5.
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ-35
p(λ)=13λ2-31λ-45-λ3+24λ+80+14λ-35
Step 5.5.2
Add -31λ and 24λ.
p(λ)=13λ2-7λ-45-λ3+80+14λ-35
Step 5.5.3
Add -7λ and 14λ.
p(λ)=13λ2+7λ-45-λ3+80-35
Step 5.5.4
Add -45 and 80.
p(λ)=13λ2+7λ-λ3+35-35
Step 5.5.5
Combine the opposite terms in 13λ2+7λ-λ3+35-35.
Step 5.5.5.1
Subtract 35 from 35.
p(λ)=13λ2+7λ-λ3+0
Step 5.5.5.2
Add 13λ2+7λ-λ3 and 0.
p(λ)=13λ2+7λ-λ3
p(λ)=13λ2+7λ-λ3
Step 5.5.6
Move 7λ.
p(λ)=13λ2-λ3+7λ
Step 5.5.7
Reorder 13λ2 and -λ3.
p(λ)=-λ3+13λ2+7λ
p(λ)=-λ3+13λ2+7λ
p(λ)=-λ3+13λ2+7λ